Preparation method of phenol compound
The problem of existing catalysts failing to effectively catalyze the formation of phenol compounds in the hydrodeoxygenation reaction of syringol was solved, and high selective conversion and catalyst stability were achieved, thereby avoiding the complexity of pre-reduction treatment. .
Patent Information
- Application Number
- CN202411220000.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
AI Technical Summary
The main products of the existing catalysts in the hydrodeoxygenation reaction of syringol are cyclohexane and cyclohexanol, which fail to effectively catalyze the formation of phenol compounds, and the pre-reduction treatment of transition metal catalysts is complex and unstable.
The CoFeAg/SiO2 catalyst was prepared by equal volume impregnation method, and was used for the selective hydrodeoxygenation reaction of syringol to avoid pre-reduction treatment. The reaction conditions were 553-623K, 1.0-2.0MPa hydrogen, and the reaction was 3h-10h.
High selective conversion of phenol compounds is achieved, the catalyst performance is excellent, the product selectivity is greater than 85%, and there is no need for pre-reduction treatment. The reaction temperature and time are controllable to ensure the stability of the catalyst.
Smart Images

Figure BDA0005022742830000081 
Figure BDA0005022742830000082 
Figure BDA0005022742830000083
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalytic material preparation and organic synthesis, and relates to a catalyst and application thereof in the preparation of phenol compounds. Background Art
[0002] Phenol compounds are important organic chemical raw materials. They can be used to produce chemical products and intermediates such as phenolic resin, caprolactam, bisphenol A, salicylic acid, etc. They are important in the chemical raw materials, synthetic fibers, plastics, medicine, dyes and other industries. In addition, phenol can also be used as a solvent, experimental reagent and disinfectant.
[0003] 2,6-Dimethoxyphenol, also known as syringol, is a structural monomer formed by the cracking of lignin and can be obtained by converting biomass lignin. Lignin is abundant in nature and has a wide range of applications. It can replace petroleum as a raw material for biofuels or chemicals. The use of renewable resources to prepare phenol compounds is a trend in the development of biomass energy in the future and has always attracted much attention. Heterogeneous or homogeneous catalysis can achieve the important process of hydrodeoxygenation of lignin and its degradation products, and heterogeneous catalysts have been widely used in this field due to their convenient separation and easy regeneration. However, there are no reports on the production of phenolic compounds by hydrodeoxygenation of syringol in current research.
[0004] V [1] Bimetallic NiMo-supported Al2O3 microsphere catalyst (NiMo@Al2O3) was prepared by combining sol-gel and spray pyrolysis. Then, anatase TiO2 was modified onto the NiMo@Al2O3 shell to prepare NiMo@Al2O3@TiO2 microsphere catalyst. The catalyst can catalyze syringol to produce methyl-substituted cyclohexane (selectivity of about 87.7%), and the benzene ring, methoxyl group and hydroxyl group in the raw material are saturated or removed by hydrogenation. Ishikawa et al. [2] The Ru–MnOx / C catalyst was prepared by impregnation method. When the raw material was syringol, the selectivity of the main product cyclohexanol was 70%, and the benzene ring in the raw material was saturated by hydrogenation and the methoxy group was removed by hydrogenation. Guo et al. [3] Using layered double hydroxide (LDH) Ni1Co3Al2-LDH as a precursor, Ni1Co3Al2-600 (calcined at 600℃) layered catalyst was prepared. The main product of HDO reaction using syringol as raw material is also cyclohexanol (selectivity up to 90%). [4] et al. anchored Ni metal on MoS2 / C by microemulsion synthesis method, also using syringol as raw material, and the selectivity of guaiacol in the product was 25%, followed by phenol and cyclohexanol. [5]et al. prepared Ru / Ti-SiO2 catalyst by impregnation method and pre-reduced it at 250℃ for 2h, so that the conversion rate of raw material guaiacol reached 83.6% and the phenol selectivity reached 70.4%.
[0005] In summary, most of the lignin model compounds that can generate phenol are guaiacol, and most of them are noble metal catalysts. [6] et al. found that Au / TiO2 can catalyze the highly selective preparation of phenolic compounds from guaiacol with a selectivity of more than 80%, but it has no catalytic performance in the catalytic reaction of syringol. The pre-reduction step of transition metal catalysts, such as Co and Ni, during use not only complicates the catalyst preparation and maintenance process and increases energy consumption, but also the reduced catalyst may lose its activity due to oxidation during use. [7] et al. prepared Ni / MgO catalyst by deposition-precipitation method, and after pre-reduction at 500℃ for 4h before use, the raw material guaiacol was converted into phenol with a selectivity of 88.9% by promoting water splitting, selective cleavage of CO bonds and aqueous phase reforming of in-situ methanol generation. Fu [8] et al. synthesized a series of highly efficient NixCoyAl-T catalysts by coprecipitation-calcination reduction method. Under the optimized reaction conditions (180 °C, reaction time of 2 h), 2-phenoxy-1-phenylethanol was 0.5 Co 1.5 The Al-600 catalyst was fully converted, and the yields of ethylbenzene and cyclohexanol reached 95.91wt% and 85.73wt%, respectively. However, the stability of the catalyst was not ideal due to oxidation of the active components in the catalyst. Syringol, as a typical model compound of lignin, has a more complex structure than phenol and guaiacol, has greater steric hindrance, and has more reaction steps. Most of the products of the currently developed catalysts for catalyzing the hydrogenation of syringol are cyclohexane and cyclohexanol. There has been no report on the selective hydrodeoxygenation of syringol to prepare phenolic compounds using CoFeAg / SiO2 as a catalyst.
[0006] References:
[0007] [1]Vo T K.Bimetallic NiMo-supported Al2O3@SiO2core-shell microspheres with highhydrodeoxygenation efficiency toward syringol[J].Journal of Sol-GelScience and Technology,2023,105:804-813.
[0009] [2]Ishikawa M,Tamura M,Nakagawa Y,et al.Demethoxylation of guaiSiO2olandmethoxybenzenes over carbon-supported Ru-Mn catalyst[J].Applied CatalysisB:Environmental,2016,182:193-203.
[0011] [3]Guo D,Cai B,Kang R,et al.Selective hydrodeoxygenation ofguaiSiO2ol tocyclohexanol over NixCoyAlz catalysts under mild conditions[J].Journal of Analytical andApplied Pyrolysis,2023,170:105876.
[0012] [4]Mukundan S,Atanda L,Beltramini J,et al.Thermocatalytic cleavage ofC-C and C-Obonds in model compounds and kraft lignin by NiMoS2 / C nanocatalyst[J].Sustainable EnergyFuels,2019,3(5):1317-1328.
[0013] [5]Wang X,Wang Z,Zhou L,et al.Efficient hydrodeoxygenation ofguaiacol to phenolover Ru / Ti–SiO2catalysts:the significance of defect-richTiOx species[J].Green Chemistry,2022,24(15):5822-5834.
[0015] [6]Mao J, Zhou J, Xia Z, et al. Anatase TiO2activated by goldnanoparticles for selective hydrodeoxygenation ofguaiacol to phenolics[J].ACSCatalysis,2017,7(1):695-705.
[0016] [7]Ren
[0017] [8] Fu ZP, Zhao YP, Wu FP, et al. Selective hydrogenolysis of CO bonds in lignin modelcompounds and Kraft lignin over highly efficient NixCoyAlcatalysts[J]. Molecular Catalysis, 2023,547:113334. Summary of the invention
[0019] In order to overcome the deficiencies of the prior art, the present invention provides a catalyst and its application in the preparation of phenolic compounds. The present invention uses CoFeAg / SiO2 catalyst for the first time to selectively hydrodeoxygenate syringol to achieve the synthesis of the final product phenolic compounds. The catalyst preparation method provided by the present invention is simple, does not require pre-reduction treatment, has good reaction performance, and has high product selectivity.
[0020] The above object of the present invention is achieved through the following technical solutions:
[0021] The first object of the present invention is to protect a CoFeAg / SiO2 catalyst, wherein 1g SiO2 is loaded with 1.0-3.0mmol Co, 0.1-1.0mmol Fe, and 0.1-0.9mmol Ag.
[0022] The second purpose of the present invention is to protect the preparation method of the above-mentioned CoFeAg / SiO2 catalyst, and the CoFeAg / SiO2 catalyst is prepared by the equal volume impregnation method. The CoFeAg / SiO2 catalyst is prepared by measuring the water absorption of SiO2, preparing a precursor solution, equal volume impregnation, drying, and calcining.
[0023] Furthermore, the preparation method of the above-mentioned CoFeAg / SiO2 catalyst comprises the following specific steps:
[0024] S1. Determine the water absorption of SiO2: Determine the water absorption of SiO2. Weigh dry SiO2 and place it in a beaker. Use a pipette to transfer deionized water into the beaker. Follow the principle of adding small amounts multiple times and stir continuously with a glass rod. When the SiO2 in the beaker becomes slightly sticky and no water seeps out, it is saturated with water. Record the volume of water transferred in as the water absorption of SiO2.
[0025] S2. Prepare precursor solution: weigh nitrate compound and prepare 0.67-2.0 mol / L Co(NO3)2·6H2O, 0.07-0.67 mol / L Fe(NO3)3·9H2O, 0.07-0.6 mol / L AgNO3 salt solution;
[0026] S3. Equal volume impregnation: Weigh the corresponding amount of SiO2, add it to the prepared metal salt solution, so that the metal salt solution is just absorbed by SiO2, stir with a glass rod for about 10-15 minutes, then cover the beaker with tin foil with small holes, and leave the sample at room temperature for about 4-6 hours;
[0027] S4 Drying: The sample after standing in step S3 is placed in a blast drying oven and dried, and after drying, it is removed and fully ground into a powdered sample with an agate mortar;
[0028] S5. Calcination: The powdered sample prepared in step S4 is placed in a crucible and calcined in a muffle furnace under air atmosphere at a calcination temperature of 500-600°C.
[0029] The third object of the present invention is to protect the use of the CoFeAg / SiO2 catalyst prepared by the above preparation method in the preparation of phenol compounds.
[0030] The specific preparation method for preparing phenolic compounds is:
[0031] Take a high-temperature and high-pressure intermittent reactor, add 500 mg of raw material syringol, 10 ml of solvent n-dodecane, 100 mg of internal standard tetradecane, and 50-100 mg of CoFeAg / SiO2 catalyst, seal it, use 1.0-2.0 MPa hydrogen to replace the air in the reactor 3-5 times, evacuate it, introduce 0.7 MPa-2.0 MPa of hydrogen, the reaction temperature range is 553-623 K, the reaction time is 3h-10h, the stirring rate is 500-1000 rpm, and the product is obtained by cooling after the reaction.
[0032] Furthermore, the particle size of SiO2 in step S1 is 30 nm. In step S1, 1 g of dry SiO2 is weighed and placed in a beaker.
[0033] The beneficial effects of the present invention compared with the prior art are:
[0034] The present invention uses CoFeAg / SiO2 catalyst without pre-reduction treatment, and the selectivity of phenolic compounds in the final reaction product is greater than 85%. The reaction temperature is controlled at 553-623K, and syringol can be hydrogenated, wherein complete conversion can be quickly achieved at 603K, and the selectivity of phenolic compounds is relatively high. DETAILED DESCRIPTION
[0035] The present invention is described in detail below by specific examples, but the protection scope of the present invention is not limited. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels.
[0036] The contents of Co, Fe and Ag in the catalyst of the present invention can be measured by ICP, and the range of the amount of metal loaded on 1g SiO2 is: 1g SiO2 loaded Co 1.0-3.0mmol (0.2910-0.8731g), Fe 0.1-1.0mmol (0.0404-0.4040g), Ag 0.1-0.9mmol (0.0169-0.1529g), and better reaction performance can be obtained. During the reaction, the catalyst, n-dodecane, syringol and tetradecane are added to a high-temperature and high-pressure intermittent reactor, and the air in the reactor is replaced 3 times with 1.0MPa hydrogen after sealing, and 0.7MPa-2.0MPa hydrogen is introduced after emptying, the reaction temperature ranges from 553 to 623K, and the reaction is carried out for 3h to 10h. After a period of reaction, samples are taken to calculate the raw material conversion rate and the yield of each product.
[0037] Syringol conversion rate = (the amount of syringol substance at the beginning of the reaction - the amount of syringol substance at the end of the reaction) / the amount of syringol substance at the beginning of the reaction × 100%;
[0038] Phenol compound selectivity = the amount of phenol compound substance at the end of the reaction / (the amount of syringol substance at the beginning of the reaction - the amount of syringol substance at the end of the reaction) × 100%;
[0039] Among them, phenol compounds include: phenol, cresol, xylenol, and trimethylol.
[0040] Since the valence state of the loaded metal is not unique after the catalyst is calcined, the loading amount of Co, Fe and Ag in the catalyst is expressed as the mass ratio of Co, Fe, Ag elements to SiO2. The metal loading amount is reflected in the "Catalyst Composition" in the example list, such as 2Co1Fe0.5Ag / SiO2 means that 1g SiO2 is loaded with 2mmol Co, 1mmol Fe and 0.5mmol Ag.
[0041] Example 1
[0042] S1. Preparation of Catalyst
[0043] (1) First, measure the water absorption of SiO2. Weigh 1g of dry SiO2 and place it in a beaker. Use a pipette to transfer deionized water into the beaker. Follow the principle of adding small amounts and multiple times, and stir continuously with a glass rod. When the SiO2 in the beaker becomes slightly sticky and no water seeps out, it is saturated with water. Record the volume of water transferred as 1.5mL / g; this is the water absorption of SiO2.
[0044] (2) Prepare the precursor solution: weigh 0.5821 g of Co(NO3)2·6H2O, 0.0404 g of Fe(NO3)3·9H2O, and 0.0849 g of AgNO3 into a beaker, and add 1.2 mL of deionized water to dissolve them to prepare a metal salt solution;
[0045] (3) Immersion in equal volume: Weigh 1g SiO2 and add it to the prepared metal salt solution until the metal salt solution is just absorbed by the SiO2. Stir with a glass rod for about 10-15 minutes, then cover the beaker with tin foil with small holes, and leave the sample at room temperature for about 4-6 hours.
[0046] (4) Drying: Place the sample after standing in step (3) in a forced air drying oven, dry at 80° C. for 12 h, and grind into powder using a mortar.
[0047] (5) Calcination: The powdered sample prepared in step (4) was placed in a crucible and calcined in a muffle furnace. The temperature was raised at 10°C / min from room temperature to 500°C, calcined for 2h, and then naturally cooled to 110°C before the sample was taken out and sealed for storage. A 2Co0.1Fe0.5Ag / SiO2 catalyst was obtained.
[0048] The catalyst prepared in step S2 is used for the hydrodeoxygenation reaction of syringol to prepare phenol compounds.
[0049] 0.05 g of the catalyst prepared in step S1, 0.5 g of syringol, 10 ml of n-dodecane and 100 mg of tetradecane were added to a high-temperature and high-pressure batch reactor, and the air in the reactor was replaced three times with 1.0 MPa hydrogen after sealing, and 1.0 MPa of hydrogen was introduced after evacuation, the reaction temperature was 330° C., the stirring rate was 500 rpm, and the reaction was carried out for 6 hours. The reaction results are shown in Table 1.
[0050] Example 2
[0051] In step S1 of Example 1, the amount of Co(NO3)2·6H2O added was 0.2910 g; the amount of Fe(NO3)3·9H2O added was 0.0404 g; the amount of AgNO3 added was 0.0849 g, and the catalyst composition was 1Co0.1Fe0.5Ag / SiO2. Others were the same as in Example 1. The reaction results are shown in Table 1.
[0052] Example 3
[0053] In step S1 of Example 1, the amount of Co(NO3)2·6H2O added was 0.4366 g; the amount of Fe(NO3)3·9H2O added was 0.0404 g; the amount of AgNO3 added was 0.0849 g, and the catalyst composition was 1.5Co0.1Fe0.5Ag / SiO2. Others were the same as in Example 1. The reaction results are shown in Table 1.
[0054] Example 4
[0055] In step S1 of Example 1, the amount of Co(NO3)2·6H2O added was 0.8731 g; the amount of Fe(NO3)3·9H2O added was 0.0404 g; the amount of AgNO3 added was 0.0849 g, and the catalyst composition was 3Co0.1Fe0.5Ag / SiO2. Others were the same as in Example 1. The reaction results are shown in Table 1.
[0056] Example 5
[0057] In step S1 of Example 1, the amount of Co(NO3)2·6H2O added was 0.5821 g; the amount of Fe(NO3)3·9H2O added was 0.0808 g; the amount of AgNO3 added was 0.0849 g, and the catalyst composition was 2Co0.2Fe0.5Ag / SiO2. Others were the same as in Example 1. The reaction results are shown in Table 2.
[0058] Example 6
[0059] In step S1 of Example 1, the amount of Co(NO3)2·6H2O added was 0.5821 g; the amount of Fe(NO3)3·9H2O added was 0.2020 g; the amount of AgNO3 added was 0.0849 g, and the catalyst composition was 2Co0.5Fe0.5Ag / SiO2. Others were the same as in Example 1. The reaction results are shown in Table 2.
[0060] Example 7
[0061] In step S1 of Example 1, the amount of Co(NO3)2·6H2O added was 0.5821 g; the amount of Fe(NO3)3·9H2O added was 0.4040 g; the amount of AgNO3 added was 0.0849 g, and the catalyst composition was 2Co1Fe0.5Ag / SiO2. Others were the same as in Example 1. The reaction results are shown in Table 2.
[0062] Example 8
[0063] In step S1 of Example 1, the amount of Co(NO3)2·6H2O added was 0.7276 g; the amount of Fe(NO3)3·9H2O added was 0.0404 g; the amount of AgNO3 added was 0.0170 g, and the catalyst composition was 2.5Co0.1Fe0.1Ag / SiO2. Others were the same as in Example 1. The reaction results are shown in Table 3.
[0064] Example 9
[0065] In step S1 of Example 1, the amount of Co(NO3)2·6H2O added was 0.7276 g; the amount of Fe(NO3)3·9H2O added was 0.0404 g; the amount of AgNO3 added was 0.0510 g, and the catalyst composition was 2.5Co0.1Fe0.3Ag / SiO2. Others were the same as in Example 1. The reaction results are shown in Table 3.
[0066] Example 10
[0067] In step S1 of Example 1, the amount of Co(NO3)2·6H2O added was 0.7276 g; the amount of Fe(NO3)3·9H2O added was 0.0404 g; the amount of AgNO3 added was 0.0849 g, and the catalyst composition was 2.5Co0.1Fe0.5Ag / SiO2. Others were the same as in Example 1. The reaction results are shown in Table 3.
[0068] Embodiment 11
[0069] In step S1 of Example 1, the amount of Co(NO3)2·6H2O added was 0.7276 g; the amount of Fe(NO3)3·9H2O added was 0.0404 g; the amount of AgNO3 added was 0.1189 g, and the catalyst composition was 2.5Co0.1Fe0.7Ag / SiO2. Others were the same as in Example 1. The reaction results are shown in Table 3.
[0070] Example 12
[0071] In step S1 of Example 1, the amount of Co(NO3)2·6H2O added was 0.7276 g; the amount of Fe(NO3)3·9H2O added was 0.0404 g; the amount of AgNO3 added was 0.1529 g, and the catalyst composition was 2.5Co0.1Fe0.9Ag / SiO2. Others were the same as in Example 1. The reaction results are shown in Table 3.
[0072] Embodiment 13
[0073] In step S2 of Example 1, the reaction time is 3 hours. Others are the same as in Example 1. The reaction results are shown in Table 4.
[0074] Embodiment 14
[0075] In step S2 of Example 1, the reaction time is 8 hours. Others are the same as in Example 1. The reaction results are shown in Table 4.
[0076] Embodiment 15
[0077] In step S2 of Example 1, the reaction time is 10 h. Others are the same as in Example 1. The reaction results are shown in Table 4.
[0078] Example 16
[0079] In step S2 of Example 1, the reaction pressure was set to 0.7 MPa, and the rest was the same as Example 1. The reaction results are shown in Table 5.
[0080] Embodiment 17
[0081] In step S2 of Example 1, the reaction pressure was set to 1.3 MPa, and the rest was the same as Example 1. The reaction results are shown in Table 5.
[0082] Embodiment 18
[0083] In step S2 of Example 1, the reaction pressure was set to 2.0 MPa, and the rest was the same as in Example 1. The reaction results are shown in Table 5.
[0084] Embodiment 19
[0085] In step S2 of Example 1, the temperature was set to 280° C., and the rest was the same as in Example 1. The reaction results are shown in Table 6.
[0086] Embodiment 20
[0087] In step S2 of Example 1, the temperature was set to 300° C., and the rest was the same as in Example 1. The reaction results are shown in Table 6.
[0088] Embodiment 21
[0089] In step S2 of Example 1, the temperature was set to 350° C., and the rest was the same as in Example 1. The reaction results are shown in Table 6.
[0090] Embodiment 22
[0091] In step S1 of Example 1, the calcination temperature is set to 600° C., and the rest is the same as in Example 1. The reaction results are shown in Table 7.
[0092] Embodiment 23
[0093] In step S2 of Example 1, the stirring rate was set to 1000 rpm, and the rest was the same as in Example 1. The reaction results are shown in Table 8.
[0094] Embodiment 24
[0095] In step S2 of Example 1, the amount of catalyst added is 100 mg, and the rest is the same as in Example 1. The reaction results are shown in Table 9.
[0096] Comparative Example 1
[0097] In Example 1, the amount of Co(NO3)2·6H2O added in step S1 is 0.5821 g; the amount of AgNO3 added is 0.0849 g; Fe(NO3)3·9H2O is not added, the catalyst composition is 2Co0.5Ag / SiO2, the temperature in step S2 is set to 320°C, the time is set to 2h, and the rest is the same as in Example 1. The reaction results are shown in Table 9.
[0098] Comparative Example 2
[0099] In Example 1, the amount of Co(NO3)2·6H2O added in step S1 is 0.5821 g; Fe(NO3)3·9H2O and AgNO3 are not added, the catalyst composition is 2Co / SiO2, the temperature in step S2 is set to 320°C, the time is set to 2h, and the rest is the same as in Example 1. The reaction results are shown in Table 9.
[0100] Comparative Example 3
[0101] In Example 1, the amount of Co(NO3)2·6H2O added in step S1 is 0.5821 g; the amount of Fe(NO3)3·9H2O added is 0.0404 g; no AgNO3 is added, the catalyst composition is 2Co0.1Fe / SiO2, the temperature in step S2 is set to 320°C, the time is set to 2 h, and the rest is the same as in Example 1. The reaction results are shown in Table 9.
[0102] Table 1 Results of Examples 1-4
[0103]
[0104] Table 2 Results of Examples 1, 5-7
[0105]
[0106] Table 3 Results of Examples 8-12
[0107]
[0108] From the data in Table 1-3, it can be seen that metal Co is the main component that plays a catalytic role, while metal Fe mainly plays a role in inhibiting the hydrogenation of benzene rings. When the amount of metal Fe is too much, the product cyclohexanol is significantly reduced, but at the same time, the selectivity of phenol compounds is also reduced due to its inhibitory effect on the catalytic hydrogenation process. The amount of metal Ag added has no significant effect on the entire catalytic process, indicating that Ag in the catalyst is a component that has the function of reducing metal oxides and does not need to be added too much.
[0109] Table 4 Results of Examples 1, 13-15
[0110]
[0111] It can be seen from Examples 1 and 13-15 that when the reaction is carried out for 3 h at 330° C. and 1 MPa H2, the conversion rate of syringol is 95.1% and the selectivity of phenolic compounds is 59.9%; when the reaction time is increased to 6 h or more, the conversion rate of syringol reaches 100%, guaiacol is gradually and completely converted into the next product, and the selectivity of phenolic compounds is significantly improved; as the reaction time continues to increase to 10 h, the selectivity of phenolic compounds decreases slightly, and phenolic compounds are gradually converted into other products.
[0112] Table 5 Results of Examples 1, 16-18
[0113]
[0114] It can be seen from Examples 1 and 16-18 that when reacted for 6 h at 0.7 MPa-2.0 MPa and 330°C, the selectivity of phenol compounds slightly increased with the increase of H2 pressure. When the H2 pressure was 1.3 MPa, the selectivity of phenol compounds was 64.5%. Thereafter, the selectivity of phenol compounds decreased with the increase of pressure, and the selectivity of cyclohexanol increased, indicating that excessive pressure would lead to hydrogenation of benzene rings to form cyclohexanol.
[0115] Table 6 Results of Examples 1, 19-21
[0116]
[0117]
[0118] As shown in Examples 1, 19-21, when the reaction temperature is lower than 330°C, syringol can also be converted, but the conversion rate is low and the selectivity of phenolic compounds is low. When the reaction temperature reaches 330°C, syringol can achieve a 100% conversion rate and a 63.6% selectivity for phenolic compounds. When the temperature reaches 350°C, the selectivity for phenolic compounds increases slightly, indicating that high temperature is conducive to the conversion of syringol into phenolic compounds.
[0119] Table 7 Results of Examples 1 and 22
[0120]
[0121] Table 8 Results of Examples 1 and 23
[0122]
[0123] Table 9 Result table of Examples 1 and 24
[0124]
[0125] Table 9 Comparative Examples 1-3 Results
[0126]
[0127]
[0128] It can be seen from the data of Comparative Examples 1-3 that CoFe and Co alone as active components cannot efficiently catalyze the hydrogenation and deoxygenation of syringol, but when combined with Ag, the CoFeAg / SiO2 catalyst can efficiently convert syringol into phenolic compounds, and the oxygen atoms in the raw materials can be selectively hydrogenated and removed.
[0129] The above-described embodiments are only preferred embodiments of the present invention, but not all feasible embodiments of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a CoFeAg / SiO2 catalyst, characterized in that: The CoFeAg / SiO2 catalyst was prepared by an equal volume impregnation method, and the CoFeAg / SiO2 catalyst was prepared by measuring the water absorption of SiO2, preparing a precursor solution, equal volume impregnation, drying, and calcining.
2. A method for preparing a CoFeAg / SiO2 catalyst as claimed in claim 1, wherein the specific steps are: S1. Determine the water absorption of SiO2: Determine the water absorption of SiO2. Weigh dry SiO2 and place it in a beaker. Use a pipette to transfer deionized water into the beaker. Follow the principle of adding small amounts multiple times and stir continuously with a glass rod. When the SiO2 in the beaker becomes slightly sticky and no water seeps out, it is saturated with water. Record the volume of water transferred in as the water absorption of SiO2. S2. Prepare precursor solution: weigh nitrate compound and prepare 0.67-2.0 mol / L Co(NO3)2·6H2O, 0.07-0.67 mol / L Fe(NO3)3·9H2O, 0.07-0.6 mol / L AgNO3 salt solution; S3. Equal volume impregnation: Weigh the corresponding amount of SiO2, add it to the prepared metal salt solution, so that the metal salt solution is just absorbed by SiO2, stir with a glass rod for about 10-15 minutes, then cover the beaker with tin foil with small holes, and leave the sample at room temperature for about 4-6 hours; S4 Drying: The sample after standing in step S3 is placed in a blast drying oven and dried, and after drying, it is removed and fully ground into a powdered sample with an agate mortar; S5. Calcination: The powdered sample prepared in step S4 is placed in a crucible and calcined in a muffle furnace under air atmosphere at a calcination temperature of 500-600°C.
3. The CoFeAg / SiO2 catalyst prepared by the preparation method according to any one of claims 1 to 2, characterized in that: 1g SiO2 is loaded with Co 1.0~3.0mmol, Fe 0.1~1.0mmol, and Ag 0.1~0.9mmol.
4. Use of the CoFeAg / SiO2 catalyst prepared by the preparation method according to claim 1-2 in the preparation of phenolic compounds from syringol.
5. The use according to claim 4, characterized in that: The specific preparation method for preparing phenolic compounds is: Take a high-temperature and high-pressure intermittent reactor, add 500 mg of raw material syringol, 10 ml of solvent n-dodecane, 100 mg of internal standard tetradecane, and 50-100 mg of CoFeAg / SiO2 catalyst, seal it, use 1.0-2.0 MPa hydrogen to replace the air in the reactor 3-5 times, evacuate it, introduce 0.7 MPa-2.0 MPa of hydrogen, the reaction temperature range is 553-623 K, the reaction time is 3h-10h, the stirring rate is 500-1000 rpm, and the product is obtained by cooling after the reaction.
